Biomimetic synthesis of silver nanoparticles for treatment of N‐Nitrosodiethylamine‐induced hepatotoxicity. Issue 3 (24th November 2021) - Singh, Asha; Dar, Mohd Yaqoob; Nagar, Durga P.; Tomar, Rajesh S.; Shrivastava, Sadhana; Shukla, Sangeeta
Abstract: The development of bioengineered nanoparticles has attracted considerable universal attention in the field of medical science and disease treatment. Current studies were executed to evaluate the hepatoprotective activity of biosynthesized silver nanoparticles (AgNPs). Their characterization was performed by UV‐Visible analysis, fourier transform infrared spectroscopy, transmission electron microscopy (TEM), scanning electron microscope (SEM), and Zeta analyses. In in vivo studies, albino rats (180 ± 10 g) were persuaded with model hepatic toxicant N ‐nitrosodiethylamine (NDEA) and subsequently cotreated with Morus multicaulis at 100 mg/kg and AgNPs at 100 µg/kg dose. NDEA administration elevates the levels of liver function test biomarkers, which were reinstated to normal by cotreatment of test drugs. The oxidative stress and concentration of drug‐metabolizing enzyme increase after induction of toxicant (NDEA), these markers are restored toward normal after cotreatment of nano‐drug. Treatments of M. multicaulis extract did not show such significant protection. The NDEA‐treated groups showed a significant rise in the level of cytokines (interleukin [IL‐6] and IL‐10) and reached normal with subsequent treatment with AgNPs. Histopathological studies also exhibited the curative effect of AgNPs in the same manner. Thus current results strongly suggest that biomimetic AgNPs could be used as an effective drug against hepatic alteration.